Salvage Total Laryngectomy with Bilateral Deltopectoral Flap Reconstruction for Metastatic (Stage IVC) Laryngeal Carcinoma: A Case Report - Steven Yohanis Latupeirissa; I Wayan Lolik Lesmana; Eka Putra Setiawan; I Gde Ardika Nuaba; Made Lely Rahayu; I Ketut Suanda (Open Access Indonesian Journal of Medical Reviews, 2025)
The management of advanced laryngeal squamous cell carcinoma (SCC) that persists or recurs after definitive chemoradiotherapy presents a significant clinical challenge. This challenge is profoundly amplified in the setting of distant metastatic disease (Stage IVC), where the goals of treatment shift from curative intent to palliation and quality of life preservation. Surgical salvage in this context is controversial and reserved for highly selected cases with severe, unmanageable local symptoms. We present the case of a 58-year-old male, a long-term smoker, with Stage IVC (T3N2cM1) laryngeal SCC, complicated by bone metastases. He initially underwent definitive chemoradiotherapy. Ten months later, he presented with progressive local disease, including a fungating cervical mass and impending airway compromise. A palliative salvage total laryngectomy with bilateral Modified Radical Neck Dissection (MRND) was performed to control severe local symptoms. The extensive pharyngocutaneous defect was reconstructed using bilateral pedicled deltopectoral fasciocutaneous flaps. The final histopathology confirmed viable, moderately differentiated SCC with extensive cartilage invasion and, critically, a positive deep resection margin. The postoperative course was managed successfully, with the patient showing significant improvement in local symptoms and quality of life at short-term follow-up. This case highlights the complex decision-making required for palliative surgery in metastatic head and neck cancer. The discussion focuses on the justification for aggressive local intervention to palliate debilitating symptoms, the rationale for selecting the robust bilateral deltopectoral flap for reconstruction in a hostile, irradiated field, and the profound prognostic implications of a positive surgical margin in the salvage setting. In conclusion, palliative salvage total laryngectomy can be a viable strategy to improve quality of life in selected patients with Stage IVC laryngeal cancer and overwhelming local disease. However, achieving complete oncologic clearance is a formidable challenge, and management must be tailored within a multidisciplinary framework.